Analisis Pengaruh Kompetensi, Komitmen Dan Budaya Kerja Terhadap Kinerja Pegawai Dinas Kependudukan Pencatatan Sipil Kabupaten Demak - Anik Ida Iryani; Bambang Guritno; Sapto Supriyanto; Andhi Supriyadi; Dyah Palupiningtyas (Gemawisata: Jurnal Ilmiah Pariwisata, 2023)
The performance of employees in an organization is affected by many factors, among them competence, commitment, and the culture of work. This research aims to know and analyze the impact of competence, commitment, and work culture on the performance of the Department of Population and civil registration of the Demak Regency. This research used a quantitative method. Data were obtained through documentation and questionnaires. The sample of this study comprised 82 respondents. Data was collected using a questionnaire. The data were then analyzed by using a multiple linear regression equation of SPSS version 25. The research concludes that : (1) competence positively and significantly influenced the performance of employees, (2) commitment positively and significantly has no impact on the performance of employees, (3) work culture positively and significantly influence the performance in the department of population and civil registration of the Demak Regency